2014
DOI: 10.1080/00223891.2014.947650
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of External Shame: An Inside View

Abstract: The aims of this study were to investigate the construct validity of the Other as Shamer scale (OAS) using confirmatory factor analysis (CFA) and to examine the psychometric properties of its Italian version in a sample of 687 nonclinical individuals. The CFA results indicated that the hypothesized hierarchical model (with 1 higher order factor and 3 first-order factors) was the best fitting solution. Cronbach's alpha indexes, as well as test-retest stability, provided satisfactory results. Correlations of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 56 publications
4
35
0
1
Order By: Relevance
“…Such associations are similar in magnitude and directions to those found in the original OAS, as well as in the Italian version Balsamo, Macchia, et al, 2015), suggesting that individuals with higher levels of external shame, as measured by the OAS-2, also experience feelings of internal shame, depression, and anxiety symptoms.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…Such associations are similar in magnitude and directions to those found in the original OAS, as well as in the Italian version Balsamo, Macchia, et al, 2015), suggesting that individuals with higher levels of external shame, as measured by the OAS-2, also experience feelings of internal shame, depression, and anxiety symptoms.…”
Section: Discussionsupporting
confidence: 57%
“…These values were slightly higher than in the Italian 18-item OAS (Balsamo, Macchia, et al, 2015). Also, Cronbach's α of the OAS-2 (.89) total score was close to that of the longer version (.87) found in another Italian sample of 687 nonclinical adults (Balsamo, Macchia, et al, 2015), and higher than that reported in a Portuguese sample of 690 nonclinical adults, both for the short (.82) and long version (.89) (Matos et al, 2015;Matos et al, 2013). This added extra support for the reliability of the OAS-2 as a shorter measure of external shame.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…The Other As Shamer Scale (OAS; Goss et al, 1994) in its version validated in Italy (Balsamo et al, 2015). The scale includes 18 items, selected from the 25-items of the Internalized Shame Scale (ISS; Cook, 1993), and is aimed at measuring global judgments about how the self is evaluated by others.…”
Section: Methodsmentioning
confidence: 99%